Mental health literacy among primary healthcare workers in South Africa and Zambia - Korhonen Joonas; Axelin Anna; Stein Dan J; Seedat Soraya; Mwape Lonia; Jansen Ronelle; Groen Gunter; Grobler Gerhard; Jörns-Presentati Astrid; Katajisto Jouko; Lahti Mari; MEGA Consortium/Research Team (WILEY, 2022)
Background
In developing countries, mental health literacy (MHL) still needs to be improved due to the high prevalence of mental disorders. It is widely recognized that MHL can improve health outcomes for both individuals and populations. Healthcare professionals' development in MHL is crucial to the prevention of mental disorders. The aim of this study was to assess MHL of primary healthcare (PHC) workers in South Africa (SA) and Zambia and determinants thereof. Limited evidence is available on the levels of MHL among PHC workers in the sub-Saharan Africa region, which faces a large burden of mental disorders.
Methods
The study population for this cross-sectional survey comprised PHC workers (n = 250) in five provinces of SA and Zambia. MHL was measured with the Mental Health Literacy Scale (MHLS). We conducted a multivariate analysis to explore determinants of MHL.
Results
Results showed moderate MHL among PHC professionals, but with a wide range from low to high MHL. Knowledge-related items had a greater dispersion than other attributes of MHL. PHC workers with more education showed a greater ability to recognize mental health-related disorders. Those who had experience in the use of mental health-related assessment scales or screening tools reported a higher total MHL. The results confirmed strong internal consistency for the MHLS.
Conclusion
The results highlighted varying mental health perceptions and knowledge in PHC. Implementation of specifically developed formal training programs and interventions to improve MHL in PHC workers to strengthen their competence may help bridge the treatment gap.